Thermophysical Properties and Molecular Interactions of Fuel Oxygenate Mixture at Different Temperatures via Jouyban-Acree Model - Kumaar T.T.; Redrouthu R.; Kanthasamy R.; Ali I.; Ayodele B.V.; Vo D.-V.N.; Palani K.N. (American Institute of Physics Inc., 2024)
Viscosities and densities of an ethanol with fuel oxygenate at temperatures of the binary system of methyl tert butyl ether of (T = 303.15 K to 318.15 K) entire composition range and 1atm. The experimental density and viscosity results were used to calculate the excess molar volume, VE and viscosity deviation, ?? of the system. With an aim, the thermophysical properties of densities and viscosity of liquid mixture were correlated using Jouyban-Acree polynomial equation to obtain their coefficients and standard deviations. Standard deviations have been considered between the fitted outcomes and the calculated data is helpful deliberate mixing behaviour of the oxygenate mixtures. It was found that, low standard deviations < 2.50% in this case, the data found with the values correlated by the corresponding model very well. The molecular interactions existing between the components of liquid mixture were also discussed. The presences of interactions were further validated with spectroscopic analysis using FTIR and 1H-NMR. 2023 American Institute of Physics Inc.. All rights reserved.